SARS-CoV-2 associated COVID-19 in Geriatric Population: A Brief Narrative Review (2020)
Coronavirus disease 2019 caused by severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2), has emerged as a fatal pandemic and has crushed even the world’s best healthcare systems. Globally, it has affected 40,373,228 individuals and resulted in 1,119,568 deaths as of October 19, 2020. Research studies have demonstrated that geriatric population is vastly vulnerable to COVID-19 morbidity and mortality given their age and preexisting chronic comorbidities such as cardiovascular disease, hypertension, diabetes mellitus, chronic pulmonary and chronic kidney disease The data regarding susceptibility of elderly population to COVID-19 is accruing and suggests that factors like age, gender, chronic comorbidity, inflammaging, immunosenescence and renin angiotensin system may be the contributing risk factors towards COVID-19 and associated mortality in elderly population. Based on updated scientific literature, this narrative review précises the clinical presentations and underlying risk factors that might be associated with COVID-19 morbidity in geriatric population and provides informed insights, and discusses clinical presentation, psychosocial impact, mortality and potential corticosteroid treatment and prevention strategies of COVID-19 in older adults.